A magyar felsőoktatás és az egyetemirányítás változásai az Osztrák-Magyar Monarchiában - Keczer, Gabriella (Közép-Európai Közlemények, 2009)
Development of Hungarian higher education and the changes in its governance during the period of “Dualism” reflected the political conditions of the era and also the characteristics of the historical inclinations of Middle-Europe. In my paper I present the development of Hungarian universities and the changes in their (in)dependence in the period of the Austrian-Hungarian Monarchy from absolutism to the First World War.